Surface modified zinc oxide particles, dispersions, cosmetics

By attaching a silane coupling agent with an alkoxy group on the surface of zinc oxide particles and controlling its permeability coefficient, the problem of difficulty in blending surface modified zinc oxide particles in oily cosmetics is solved, and the effects of high transparency and ultraviolet shielding are achieved.

CN115485242BActive Publication Date: 2025-03-18SUMITOMO OSAKA CEMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080100265.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-04-30
Publication Date
2025-03-18
Estimated Expiration
2040-04-30

AI Technical Summary

Technical Problem

The prior art is difficult to effectively blend surface modified zinc oxide particles into oily cosmetics, resulting in insufficient transparency and ultraviolet shielding.

Method used

Surface modified zinc oxide particles that can be easily dispersed in oily cosmetics are prepared by attaching a silane coupling agent with an alkoxy group on the surface of the zinc oxide particles and controlling its permeability coefficient to be within a range of 5.0×10-2g2/s or more and 1.0×102g2/s or less.

Benefits of technology

It realizes effective dispersion of surface modified zinc oxide particles in cosmetics with less energy, improving the transparency and ultraviolet shielding of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115485242B_ABST
    Figure CN115485242B_ABST
Patent Text Reader

Abstract

A surface-modified zinc oxide particle having a silane coupling agent on the surface, wherein the silane coupling agent has an alkoxy group, wherein the surface-modified zinc oxide particle is characterized in that a permeation rate coefficient A of cyclopentasiloxane represented by A in the following formula (1) relative to the surface-modified zinc oxide particle is 5.0×10 ‑2 g 2 / s or more and 1.0×10 2 g 2 / s or less. Where W is the penetration weight in g, and t is the time in s. 2 =A·t(1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to surface modified zinc oxide particles, dispersion liquid and cosmetic material. Background Art

[0002] It is known that zinc oxide has excellent ultraviolet shielding ability, high gas barrier properties and high transparency. Therefore, particles formed of zinc oxide (hereinafter referred to as "zinc oxide particles") are used as a forming material for various raw materials that have functions such as ultraviolet shielding or gas barrier and require transparency. Examples of such raw materials include ultraviolet shielding films, ultraviolet shielding glass, cosmetics, gas barrier films, and the like.

[0003] As a method for making the above-mentioned various raw materials transparent, for example, a method of reducing the primary particle size of zinc oxide particles as a forming material can be cited. As a method for reducing the primary particle size of zinc oxide particles, various methods such as thermal decomposition method and gas phase method have been studied (for example, refer to Patent Documents 1 and 2).

[0004] When zinc oxide particles are applied to cosmetics, surface treatment of the zinc oxide particles is performed in order to make the surface of the zinc oxide particles match the properties of the cosmetics or to suppress the catalytic activity of the zinc oxide particles.

[0005] When zinc oxide particles are incorporated into oily cosmetics or emulsion oil phases, zinc oxide particles having alkoxy groups on the surface are used after surface treatment with a silane coupling agent having an alkoxy group or the like (see, for example, Patent Documents 3 and 4).

[0006] In the following description, zinc oxide particles having a silane coupling agent on the surface are referred to as surface-modified zinc oxide particles.

[0007] The surface-modified zinc oxide particles are directly blended into cosmetics, or in the form of a dispersion dispersed in a dispersion medium.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2002-284527

[0011] Patent Document 2: Japanese Patent Application Publication No. 2000-95519

[0012] Patent Document 3: International Publication No. 2017 / 130632

[0013] Patent Document 4: Japanese Patent Application Publication No. 2007-51188 Summary of the invention

[0014] Problem that the invention aims to solve

[0015] However, even zinc oxide particles having a silane coupling agent on the surface require a large amount of dispersibility in order to be blended into an oily cosmetic, and even if blended into an oily cosmetic, sufficient transparency and ultraviolet shielding properties cannot be obtained.

[0016] The present invention has been made in view of the above circumstances, and its object is to provide a surface-modified zinc oxide particle which can be easily blended into an oily cosmetic and has excellent transparency and ultraviolet shielding properties. Another object is to provide a dispersion liquid and a cosmetic containing such surface-modified zinc oxide particles.

[0017] Solutions for solving problems

[0018] In order to solve the above problems, the first aspect of the present invention provides a surface-modified zinc oxide particle having a silane coupling agent on the surface, wherein the silane coupling agent has an alkoxy group, wherein the surface-modified zinc oxide particle is characterized in that the permeation rate coefficient A of the cyclopentasiloxane represented by A in the following formula (1) with respect to the surface-modified zinc oxide particle is 5.0×10 - 2 g 2 / s or more and 1.0×10 2 g 2 / s or less.

[0019] W 2 =A·t (1)

[0020] (W is the penetration weight (unit: g), and t is the time (unit: s).)

[0021] In the first aspect of the present invention, the surface-modified zinc oxide particles may be constituted such that: * a * b * b in the chromaticity diagram of the color system * It is 4.0 or more and 18 or less.

[0022] In the first aspect of the present invention, the silane coupling agent may be at least one selected from the group consisting of alkylalkoxysilane, allylalkoxysilane, polysiloxane having an alkyl group in a side chain, and polysiloxane having an allyl group in a side chain.

[0023] In the first aspect of the present invention, the silane coupling agent may be at least one selected from the group consisting of octyltriethoxysilane, octyltrimethoxysilane, and a dimethoxydiphenylsilane-triethoxyoctanoylsilane crosslinked polymer.

[0024] In order to solve the above-mentioned problems, a second aspect of the present invention provides a dispersion liquid containing the above-mentioned surface-modified zinc oxide particles and a dispersion medium.

[0025] In order to solve the above-mentioned problems, a third aspect of the present invention provides a cosmetic comprising at least one selected from the group consisting of the above-mentioned surface-modified zinc oxide particles and the above-mentioned dispersion.

[0026] In order to solve the above-mentioned problems, a fourth aspect of the present invention provides a method for selecting the above-mentioned surface-modified zinc oxide particles.

[0027] The fourth aspect of the method for selecting surface-modified zinc oxide particles comprises: preparing surface-modified zinc oxide particles having a silane coupling agent on the surface, the silane coupling agent having an alkoxy group; evaluating the surface-modified zinc oxide particles to obtain a permeation rate coefficient A of cyclopentasiloxane represented by A in the following formula (1) relative to the surface-modified zinc oxide particles, and determining whether the coefficient A is within 5.0×10 -2 g 2 / s or more and 1.0×10 2 g 2 / s or less; and

[0028] W 2 =A·t (1)

[0029] (W is the penetration weight (unit: g), and t is the time (unit: s).)

[0030] When the above-mentioned A is within the above-mentioned range, the step of surface-modified zinc oxide particles is selected.

[0031] Effects of the Invention

[0032] According to the present invention, it is possible to provide surface-modified zinc oxide particles which can be dispersed in cosmetics with less energy and have excellent transparency and ultraviolet shielding properties. In addition, according to the present invention, it is possible to provide a dispersion liquid and a cosmetic containing such surface-modified zinc oxide particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a figure which shows the dispersion state of the surface-modified zinc oxide particles of Example 4 (right) and Comparative Example 2 (left). DETAILED DESCRIPTION

[0034] Embodiments of the surface-modified zinc oxide particles of the present invention will be described.

[0035] In addition, in the present embodiment, specific description is given for better understanding of the purpose of the invention, and unless otherwise specified, the present invention is not limited. The present invention may change, omit, replace, add, etc. to numerical values, amounts, materials, types, time, temperature, sequence, etc. within the scope of the purpose.

[0036] [Surface modified zinc oxide particles]

[0037] The surface-modified zinc oxide particles of the present embodiment are surface-modified zinc oxide particles having a silane coupling agent on the surface, wherein the silane coupling agent has an alkoxy group. Furthermore, the permeation rate coefficient of cyclopentasiloxane with respect to the surface-modified zinc oxide particles (A in the following formula (1)) is 5.0×10 -2 g 2 / s or more and 1.0×10 2 g 2 / s or less.

[0038] W 2 =A·t (1)

[0039] (W is the penetration weight (unit: g), and t is the time (unit: s).)

[0040] The permeation rate coefficient of cyclopentasiloxane relative to the surface-modified zinc oxide particles can be calculated by the permeation weight detection method. Specifically, a device capable of detecting the permeation weight (e.g., PENETO ANALYZER (model: PNT-N) manufactured by Hosokawa Micron Group Co., Ltd.) can be used to calculate. A cylindrical pool with a diameter of 36 mm and a filter paper as the bottom surface, a device capable of detecting the weight change of the cylindrical pool and / or the cyclopentasiloxane described later and the time elapsed, a container containing cyclopentasiloxane, and a part that contacts the container with the filter paper by actions such as lifting can be used to obtain the permeation rate coefficient. Specifically, after 10 g of surface-modified zinc oxide particles can be placed in the cylindrical pool, cyclopentasiloxane can be contacted with the surface of the filter paper to measure the weight change and time elapsed of the pool and / or cyclopentasiloxane, and A can be obtained according to the formula (1).

[0041] When using PENETO ANALYZER manufactured by Hosokawa Micron Corporation, the measurement can be performed, for example, as follows.

[0042] Prepare the measurement cell in the following order.

[0043] About 10 g of surface-modified zinc oxide particles were filled into a cylindrical cell with a diameter of 36 mm and a filter paper (model: quantitative filter paper No. 7, manufactured by ADVANTEC) on the bottom. 200 g of aluminum weights were placed on the filled surface-modified zinc oxide particles and allowed to stand for 1 minute.

[0044] Next, after removing the weight, the cyclopentasiloxane as the liquid medium was raised by a lifting device to contact the bottom surface (filter paper) of the cell to measure the time and weight change, thereby measuring the permeation rate. The permeation rate coefficient was obtained from the measured time and weight change.

[0045] If the penetration rate coefficient of cyclopentasiloxane to surface-modified zinc oxide particles is 5.0×10 -2 g 2 / s or more, the surface-modified zinc oxide particles have high wettability with respect to cyclopentasiloxane. Therefore, they can be easily dispersed in oily cosmetics.

[0046] If the penetration rate coefficient of cyclopentasiloxane to surface-modified zinc oxide particles is 1.0×10 2 g 2 / s or less, the surface-modified zinc oxide particles can suppress the increase in viscosity caused by oil absorption when blended into cosmetics. In addition, oil absorption means that the surface-modified zinc oxide particles absorb the oil component in the cosmetics.

[0047] Cyclopentasiloxane is a solvent commonly used in oily cosmetics. Therefore, since it can be considered that surface-modified zinc oxide particles with high wettability to cyclopentasiloxane are easily dispersed in oily cosmetics, cyclopentasiloxane was used.

[0048] Here, "easily dispersible" means that a dispersion liquid or composition having a small dispersed particle size can be obtained with weak dispersion energy. Surface-modified zinc oxide particles having a small dispersed particle size are excellent in transparency and ultraviolet shielding properties when incorporated into cosmetics.

[0049] The surface-modified zinc oxide particles of the present embodiment are surface-modified zinc oxide particles having a silane coupling agent having an alkoxy group on the surface. That is, the surface-modified zinc oxide particles of the present embodiment are zinc oxide particles having a silane coupling agent having an alkoxy group attached to at least a portion of the surface.

[0050] The specific surface area of ​​the surface-modified zinc oxide particles of this embodiment can be arbitrarily selected, but is preferably 1.5 m 2 / g or more, more preferably 2.5m 2 / g or more, more preferably 4m 2 / g or more. In addition, the specific surface area of ​​the surface-modified zinc oxide particles can be, for example, 55 m 2 / g or less, preferably 50m 2 / g or less, more preferably 45m 2 If necessary, the specific surface area of ​​the surface-modified zinc oxide particles may be 40 m 2 / g or less, and can also be 30m 2 / g or less, and can also be 10m 2 The above upper limit value and lower limit value of the specific surface area of ​​the surface-modified zinc oxide particles may be arbitrarily combined.

[0051] If the specific surface area of ​​the surface-modified zinc oxide particles is 1.5 m 2 / g or more and 50m2 / g or less, the transparency and ultraviolet shielding properties when blended into cosmetics are excellent.

[0052] In order to improve the transparency when blended into cosmetics, the specific surface area of ​​the surface-modified zinc oxide particles is preferably 8 m 2 / g or more, more preferably 15m 2 / g or more, more preferably 20m 2 / g or above.

[0053] For example, the specific surface area of ​​surface-modified zinc oxide particles is 20 m 2 / g or more and 50m 2 / g or less, preferably 20m 2 / g or more and 48m 2 / g or less, more preferably 20m 2 / g or more and 46m 2 / g or less. It can also be 20.0m 2 / g or more and 30.0m 2 / g or less, 20.0m 2 / g or above and 38.0m 2 / g or less or 20.0m 2 / g or above and 44.0m 2 / g or less.

[0054] By making the specific surface area of ​​the surface-modified zinc oxide particles 20 m 2 / g or more, when blended into oily cosmetics containing silicone oil or the like, cosmetics with excellent transparency can be obtained. On the other hand, by making the specific surface area of ​​the surface-modified zinc oxide particles 50m 2 / g or less, the surface energy of the particles will not be too large, and thus the particles can be blended into oily cosmetics (hereinafter, sometimes simply referred to as "cosmetics") with less energy.

[0055] On the other hand, in order to increase the UVA-band shielding property when blended into cosmetics, the specific surface area of ​​the surface-modified zinc oxide particles is preferably less than 20 m 2 / g, more preferably 15m 2 / g or less, more preferably 8m 2 / g or less.

[0056] For example, the specific surface area of ​​the surface-modified zinc oxide particles is preferably 1.5 m 2 / g or more and less than 20m 2 / g, more preferably 1.5m 2 / g or more and 15m 2 / g or less, more preferably 1.5m 2 / g or more and 8m2 / g or less.

[0057] By making the specific surface area of ​​the surface-modified zinc oxide particles 1.5 m 2 / g or more, when blended into oily cosmetics containing silicone oil or the like, a transparent cosmetic can be obtained. On the other hand, by making the specific surface area of ​​the surface-modified zinc oxide particles less than 20 m 2 / g, the surface energy of the particles is not too large, and thus the particles can be blended into oily cosmetics with less energy, and cosmetics having excellent ultraviolet shielding properties in the UVA region can be obtained.

[0058] The specific surface area (unit: m 2 / g) is the BET specific surface area obtained by the BET method.

[0059] As a method for measuring the specific surface area of ​​the surface-modified zinc oxide particles, for example, there is a BET method using a fully automatic specific surface area measuring apparatus (trade name: Macsorb HM Model-1201, manufactured by MOUNTECH Corporation).

[0060] Here, the reason why the surface-modified zinc oxide particles according to the present embodiment can be dispersed in an oil-based cosmetic with a relatively small amount of energy and have excellent ultraviolet shielding properties is described.

[0061] The present inventors have found that when zinc oxide particles are surface-treated with a silane coupling agent having an alkoxy group (hereinafter, sometimes referred to as a "silane coupling agent"), the zinc oxide particles and the silane coupling agent are dispersed with high energy using a disperser having a large dispersion energy such as a bead mill, and as a result, excellent surface-modified zinc oxide particles that can be easily dispersed in a silicone-containing cosmetic can be obtained. Here, the above-mentioned dispersion energy refers to the energy required to disperse the zinc oxide particles in a solvent using the silane coupling agent. In other words, it refers to the energy to the extent that the agglomerated zinc oxide particles are disintegrated.

[0062] The details of this mechanism are presumed to be as follows.

[0063] The specific surface area is 1.5m 2 / g or more and 50m 2 Zinc oxide particles with a specific surface area of ​​20 m 2 / g or more and 50m 2 / g or less zinc oxide particles are more likely to condense with each other. Therefore, in the past, a surface treatment was performed using a silane coupling agent in a condensed state. However, if such particles that have been surface-treated in a state where the particles are condensed with each other are mixed with the oil component of an oily cosmetic, the particles are dispersed while maintaining the condensed state. Therefore, the transparency and ultraviolet shielding properties are deteriorated due to the condensation. In order to prevent the deterioration as described above, it is necessary to dismantle the condensation of the particles, so that more dispersion energy is required when making an oily cosmetic. However, even if the transparency and ultraviolet shielding properties are improved by dismantling the condensation with high energy, the surface treatment state of the dismantled zinc oxide particles is not uniform because the condensation of the surface-treated condensate is dismantled while maintaining the condensed state. As a result, the dispersion stability of the surface-modified zinc oxide particles in the oily cosmetic is impaired.

[0064] However, by dispersing the zinc oxide particles in a solvent at high energy, the surface treatment can be performed with a silane coupling agent in a state where the aggregation of the zinc oxide particles is broken up, and it is presumed that the silane coupling agent can be substantially uniformly present on the entire surface of the zinc oxide particles. Therefore, if the surface-modified zinc oxide particles in this state are mixed with an oil component, the wettability of all parts of the surface of the zinc oxide particles with the oil component is good, and the particles can be dispersed in the oil component at low energy. In addition, the silane coupling agent is substantially uniformly present on the surface of the zinc oxide particles, so it is presumed that a cosmetic material can be obtained in which the aggregation of the surface-modified zinc oxide particles is also suppressed and which has excellent transparency, ultraviolet shielding properties, and dispersion stability.

[0065] However, it is very difficult to directly confirm that the silane coupling agent is uniformly present on the surface of the zinc oxide particles. In the present embodiment, it is presumed that the effect of being able to easily disperse the surface-modified zinc oxide particles in the solvent is manifested by a complex linkage of multiple factors, specifically, by a complex linkage of multiple factors such as the shape of the zinc oxide particles, the specific surface area, the particle size distribution, the degree of hydrolysis of the silane coupling agent having an alkoxy group, the degree of attachment of the silane coupling agent having an alkoxy group to the zinc oxide particles, or the attachment rate of the silane coupling agent having an alkoxy group on the zinc oxide particles. Therefore, it is considered almost impossible to directly determine the characteristics of the surface-modified zinc oxide particles of the present embodiment based on the state of the surface of the zinc oxide particles surface-modified by the silane coupling agent having an alkoxy group.

[0066] Therefore, the present inventors have conducted various studies and found that, focusing on the wettability of surface-modified zinc oxide particles, surface-modified zinc oxide particles that are easily dispersed in oily cosmetics and have excellent ultraviolet shielding properties can be obtained by treating the surface of zinc oxide particles with a silane coupling agent at high energy to achieve target dispersibility. In other words, the value of the penetration rate coefficient obtained by the above-mentioned measurement method can be considered to be an indicator of whether the silane coupling agent is uniformly present on the surface of the zinc oxide particles.

[0067] In the present embodiment, surface-modified zinc oxide particles preferably used in cosmetics are used, and therefore zinc oxide particles are used as particles, a silane coupling agent having an alkoxy group is used as a surface-modifying material, and cyclopentasiloxane is used as a solvent as an index for evaluating the state of surface treatment.

[0068] However, the evaluation method of the surface treatment state of the present embodiment is not limited to the combination of zinc oxide particles and a silane coupling agent having an alkoxy group, and can also be extended to particles and surface modification materials. That is, by selecting a solvent and measuring the penetration rate coefficient of the surface-modified particles with the surface modification agent relative to the selected solvent, the uniformity of the surface treatment can be used as an indicator.

[0069] When the surface treatment with a silane coupling agent is performed at high energy, the L of the surface-modified zinc oxide particles increases as the surface treatment progresses. * a * b * b in the chromaticity diagram of the color system * (hereinafter, sometimes referred to as "b * ”.) is larger than the b of zinc oxide particles before surface treatment. * Therefore, the surface modified zinc oxide particles b * It serves as an indicator of surface treatment with a silane coupling agent.

[0070] The surface modified zinc oxide particles of this embodiment have * It is preferably 4.0 to 18, more preferably 4.5 to 16. It may be 4.0 to 12, 4.5 to 11, or 5.0 to 10.0, etc., as required. * The difference may be, for example, 0.5 to 8.0, 2.0 to 8.0, or 3.0 to 7.5, but is not limited to these values.

[0071] As the b of the surface modified zinc oxide particles * The method can utilize a known method such as using a spectrocolorimeter, and for example, a spectrocolorimeter (Spectro Color Meter SE7700 manufactured by Nippon Denshoku Industries Co., Ltd.) can be used.

[0072] In this embodiment, "having a silane coupling agent on the surface" means that the silane coupling agent and the zinc oxide particles are in contact or bonded by the interaction therebetween. As contact, for example, physical adsorption can be cited. And as bonding, for example, ionic bonding, hydrogen bonding, covalent bonding, etc. can be cited.

[0073] The amount of the silane coupling agent in the surface-modified zinc oxide particles can be appropriately adjusted for use according to the specific surface area of ​​the zinc oxide particles and the hydrophobicity of the oily cosmetics to be blended. For example, the amount of the silane coupling agent in the surface-modified zinc oxide particles is preferably 1% by mass or more and 20% by mass or less relative to the zinc oxide particles, more preferably 2% by mass or more and 18% by mass or less, and further preferably 3% by mass or more and 16% by mass or less. As required, it can also be 3% by mass or more and 8% by mass or more and 5% by mass or more and 10% by mass or less. However, it is not limited to the examples described above.

[0074] The amount of the silane coupling agent in the surface-modified zinc oxide particles can be calculated by, for example, quantitatively analyzing the amount of Si in the surface-modified zinc oxide particles using an inductively coupled plasma emission spectrometer.

[0075] "Zinc Oxide Particles"

[0076] The specific surface area of ​​the zinc oxide particles (before surface treatment) of this embodiment can be arbitrarily selected, but is preferably 1.5 m 2 / g or more, more preferably 2.5m 2 / g or more, more preferably 4m 2 / g or more. In addition, the specific surface area of ​​the zinc oxide particles is preferably 50 m 2 / g or less, more preferably 45m 2 If necessary, the specific surface area of ​​the zinc oxide particles may be 40 m 2 / g or less, and can also be 30m 2 / g or less, and can also be 10m 2 / g or less.

[0077] The specific surface area of ​​the zinc oxide particles before the surface treatment and the specific surface area of ​​the surface-modified zinc oxide particles are slightly different depending on the attachment method of the silane coupling agent, but the change is not large.

[0078] Therefore, in order to obtain surface-modified zinc oxide particles having a desired specific surface area, zinc oxide particles having the desired specific surface area may be used. That is, the surface-modified zinc oxide particles of the present embodiment may preferably have the same value or range as the preferred specific surface area of ​​the zinc oxide particles described above.

[0079] L of zinc oxide particles before treatment * a* b * b in the chromaticity diagram of the color system * Preferably, it is 10 or less. * For zinc oxide particles within the above range, the surface modified zinc oxide particles have a b * The above range (i.e., 4.0 or more and 18 or less) can also be achieved, and the b of the surface-modified zinc oxide particles * Greater than the b of zinc oxide particles before surface treatment * As a result, the yellowness can be suppressed to a level suitable for cosmetics. * The lower limit of is not particularly limited, and may be 0, 1.0, or 1.5.

[0080] "Silane coupling agent having an alkoxy group"

[0081] The silane coupling agent having an alkoxy group may be arbitrarily selected, and preferably, among the silane coupling agents represented by the following general formula (1), silane coupling agents that can be used in cosmetics are used.

[0082] R 1 Si(OR 2 )3(1)

[0083] (R 1 represents an alkyl group, a fluoroalkyl group or a phenyl group having 1 to 18 carbon atoms, and R 2 represents an alkyl group having 1 to 4 carbon atoms. )

[0084] As such a silane coupling agent, at least one selected from the group consisting of alkylalkoxysilane, allylalkoxysilane, polysiloxane having an alkyl group in a side chain, and polysiloxane having an allyl group in a side chain is preferred.

[0085] Examples of the alkylalkoxysilane include methyltrimethoxysilane, methyltriethoxysilane, methyltripropoxysilane, methyltributoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltripropoxysilane, ethyltributoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-propyltripropoxysilane, n-propyltributoxysilane, isopropyltrimethoxysilane, isopropyltriethoxysilane, isopropyltripropoxysilane, isopropyltributoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, phenyltripropoxysilane, phenyltributoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane (triethoxyoctanoylsilane), and n-octadecyltrimethoxysilane.

[0086] As the silane coupling agent, for example, a polymer-type silane coupling agent having a siloxane skeleton as the main chain and having an alkoxy group and an acrylic group in the molecular structure, such as dimethoxydiphenylsilane-triethoxycaprylylsilane crosslinked polymer, triethoxysilylethyl polydimethylsiloxyethyl polydimethylsiloxane, and triethoxysilylethyl polydimethylsiloxyethylhexyl polydimethylsiloxane, can be used.

[0087] As the silane coupling agent, for example, fluoroalkylalkoxysilane such as trifluoropropyltrimethoxysilane, perfluorooctyltriethoxysilane, and tridecafluorooctyltriethoxysilane may be used.

[0088] These silane coupling agents may be used alone or in combination of two or more.

[0089] Among the above-mentioned silane coupling agents, silane coupling agents having an octyl group in the molecule are more preferred. Specifically, silane coupling agents that can cope with a wide range of polar oil phases from natural oils or ester oils to silicone oils are more preferred. As such a silane coupling agent, at least one selected from the group consisting of n-octyltriethoxysilane, n-octyltrimethoxysilane, and dimethoxydiphenylsilane-triethoxyoctanoylsilane crosslinked polymers is particularly preferred.

[0090] These silane coupling agents may be used alone or in combination of two or more.

[0091] In the surface-modified zinc oxide particles of the present embodiment, the zinc oxide particles may be surface-treated with a treatment agent other than the silane coupling agent, which is a surface treatment agent used in cosmetics, in addition to the silane coupling agent, within a range that does not inhibit the properties of the surface-modified zinc oxide particles.

[0092] Examples of the surface treatment agent other than the silane coupling agent include inorganic materials such as silica and alumina, and organic materials such as silicone compounds, fatty acids, fatty acid soaps, fatty acid esters, and organic titanate compounds.

[0093] The permeation rate coefficient of cyclopentasiloxane (A in the above formula (1)) of the surface-modified zinc oxide particles of the present embodiment is 5.0×10 -2 g 2 / s or more and 1.0×10 2 g 2 Therefore, the surface-modified zinc oxide particles according to the present embodiment have high wettability to cyclopentasiloxane, can be easily dispersed in oily cosmetics, and can suppress an increase in viscosity due to oil absorption when blended into cosmetics.

[0094] "Method for producing surface-modified zinc oxide particles"

[0095] The method for producing surface-modified zinc oxide particles of the present embodiment includes: placing a silane coupling agent having an alkoxy group, a solvent, and zinc oxide particles in a disperser to prepare a mixed solution; and dispersing the mixed solution at a predetermined energy or higher.

[0096] The step of preparing the mixed solution may further contain water.

[0097] The step of preparing the mixed solution may further contain a catalyst.

[0098] A heating step may be performed after the above-mentioned dispersion treatment step.

[0099] The drying step may be performed after the above-mentioned dispersion treatment step or after the heating step.

[0100] The crushing process may be performed after the heating process or after the drying process.

[0101] The silane coupling agent having an alkoxy group and the zinc oxide particles used in the production method can be exactly the same as those described above, and therefore, description thereof will be omitted.

[0102] “Mixed liquid preparation process”

[0103] In the process of preparing the mixed solution, a silane coupling agent, a solvent and zinc oxide particles are placed in a disperser. Furthermore, pure water or a catalyst may be added as needed. These materials may be placed at the same time or sequentially. The order in which these materials are placed is not particularly limited. After being placed in the disperser, the mixture may be kept in its original state without stirring, or may be simply stirred. Furthermore, these materials may be mixed in advance before being placed in the dispersion and then placed in the disperser.

[0104] "Solvent"

[0105] The solvent is not particularly limited as long as it is a solvent that can be mixed with the silane coupling agent. As the solvent, for example, alcohols such as methanol, ethanol, n-propanol, isopropanol, and n-butanol, esters such as ethyl acetate and butyl acetate, or n-hexane, toluene, and xylene can be cited. Among these solvents, alcohols are preferred from the viewpoint of being miscible with water, and isopropanol is particularly preferred among the alcohols.

[0106] The content of the solvent in the mixed solution can be arbitrarily selected, but is preferably 40% by mass or more in order to suppress aggregation of zinc oxide particles. The upper limit of the content of the solvent is not particularly limited, but is preferably 95% by mass or less from the viewpoint of production efficiency.

[0107] The content of the zinc oxide particles in the mixed solution can be arbitrarily selected, but from the viewpoint of both suppressing the aggregation of the zinc oxide particles and production efficiency, it is preferably 1% by mass or more and 55% by mass or less, and more preferably 10% by mass or more and 50% by mass or less. The content may also be 15% by mass or more and 45% by mass or less, 20% by mass or more and 40% by mass or less, or 25% by mass or more and 35% by mass or less.

[0108] The content of the silane coupling agent in the mixed solution can be arbitrarily selected, as long as it is appropriately adjusted to impart the desired hydrophobicity to the zinc oxide particles. For example, the amount of the silane coupling agent in the surface-modified zinc oxide particles can be adjusted and mixed to be 1% by mass or more and 20% by mass or less. As required, the amount can also be 1% by mass or more and 10% by mass or less or 1% by mass or more and 5% by mass or less. The content of the silane coupling agent in the mixed solution can be, for example, 0.01% by mass or more and 11% by mass or less or 0.1% by mass or more and 10% by mass or less.

[0109] The amount of pure water can be arbitrarily selected, and is preferably appropriately adjusted to an amount required to promote the hydrolysis reaction of the silane coupling agent.

[0110] The amount of the catalyst can be arbitrarily selected, and is preferably appropriately adjusted to be an amount required to promote the hydrolysis reaction of the silane coupling agent. The catalyst can be an acid or a base.

[0111] Examples of the acid include inorganic acids such as hydrochloric acid, hydrobromic acid, hydroiodic acid, sulfuric acid, nitric acid, boric acid, and phosphoric acid, and organic acids such as acetic acid, citric acid, and formic acid. These acids may be used alone or in combination of two or more.

[0112] Examples of the base include sodium hydroxide, potassium hydroxide, barium hydroxide, calcium hydroxide, ammonia, amines, etc. These bases may be used alone or in combination of two or more.

[0113] "Disperser"

[0114] The disperser is not particularly limited as long as it can impart to the mixed liquid a dispersing energy of a degree that allows the zinc oxide particles to be surface treated while breaking up aggregation of the particles.

[0115] Examples of such dispersers include colloid mills, roll mills, ultrasonic dispersers, high pressure homogenizers, ultimizers, rotary mills, planetary mills, bead mills, sand mills, etc. As the dispersion medium used in the dispersion device requiring a dispersion medium, for example, granular bodies having a predetermined hardness, such as zirconium oxide, glass, aluminum oxide, titanium dioxide, and silicon nitride, can be used.

[0116] "Dispersed process"

[0117] In the dispersing step, the mixed solution is dispersed using a disperser at a predetermined energy or more to obtain surface-modified zinc oxide particles.

[0118] The energy given to the mixed solution can be appropriately adjusted according to the size of the dispersion machine. Therefore, the conditions for dispersion can be appropriately selected. For example, when utilizing a mill, for example, using a container with a capacity of about 1L and utilizing a bead mill for dispersion treatment, it is preferred to carry out dispersion treatment for more than 1 hour and less than 10 hours with a rotating speed of more than 500rpm. However, the conditions can be selected as needed and are not limited to the conditions.

[0119] Furthermore, when a mill is used, for example, a bead mill is used to perform dispersion treatment using a container having a capacity of about 1 L, the dispersion energy imparted to the mixed solution is preferably, for example, 100 W·h / kg or more and 600 W·h / kg or less. However, the conditions can be selected as needed and are not limited to the above conditions.

[0120] The crushing force of the bead mill depends on the centrifugal force of the beads on the outer periphery of the disk or pin in the mill. Therefore, it is preferable to calculate the product (impulse) of the centrifugal force and the dispersion time when the bead weight is the total weight of the beads in the mill to be 0.5×10 6 N·s or more and 100×10 6 Dispersion processing below N·s.

[0121] Furthermore, the surface modified zinc oxide particles can be dispersed to the * At this time, the b value of the zinc oxide particles can be measured by extracting a small amount of the zinc oxide particles in the dispersion treatment and using a spectrocolorimeter to measure the b value of the zinc oxide particles. * To confirm the extent of the dispersion process.

[0122] The temperature in the dispersion step is not particularly limited, but is preferably, for example, 20° C. or higher and 45° C. or lower.

[0123] "Heating process"

[0124] From the viewpoint of accelerating the surface treatment step of the silane coupling agent, the heating step may be performed simultaneously with the dispersion step or after the dispersion step.

[0125] The heating temperature is not particularly limited as long as it is a temperature that promotes the surface treatment, and is preferably, for example, 40° C. to 150° C. If necessary, it may be 40° C. to 80° C. or 60 to 100° C.

[0126] Drying process

[0127] The liquid after the dispersion treatment is preferably dried using a drying device. In addition, solid-liquid separation and other treatments to shorten the drying time may be performed before drying. The drying device is not particularly limited, and examples thereof include a box dryer, a vacuum dryer, a vibration dryer, a fluidized bed dryer, a belt dryer, an evaporator, a Nauta mixer, a Henschel mixer, a RIBOCONE, a paddle dryer, a spray dryer, a slurry dryer, a flash dryer, a rotary dryer, and the like.

[0128] The drying temperature is not particularly limited as long as it is a temperature at which the solvent can be removed, and is preferably, for example, 50° C. to 200° C., and may be 60° C. to 150° C. or 70° C. to 120° C., etc.

[0129] Crushing process

[0130] The dried surface-modified zinc oxide particles can be crushed using a crusher. Any crusher can be selected, for example, an atomizer, a hammer mill, a jet mill, an impeller mill, a pin mill, etc. The crushing process can suppress the roughness of the surface-modified zinc oxide particles when mixed into cosmetics. That is, the feeling of use when the surface-modified zinc oxide particles are used in cosmetics can be improved.

[0131] "Select Operation"

[0132] In addition, in the present invention, the preferred surface-modified zinc oxide particles can be selected by the following method.

[0133] First, surface-modified zinc oxide particles having a silane coupling agent having an alkoxy group on the surface are prepared. The surface-modified zinc oxide particles are evaluated to obtain a permeation rate coefficient A of cyclopentasiloxane represented by A in the following formula (1) relative to the surface-modified zinc oxide particles, and it is determined whether the coefficient A is within 5.0×10 -2 g 2 / s or more and 1.0×10 2 g 2 When A is within the above range, the surface-modified zinc oxide particles can be preferably selected.

[0134] W 2 =A·t (1)

[0135] (W is the penetration weight (unit: g), and t is the time (unit: s).)

[0136] In addition, the determination process can be performed using, for example, a cylindrical pool with a diameter of 36 mm and a filter paper as the bottom surface, a container containing cyclopentasiloxane, a component for raising and lowering the container so that the cyclopentasiloxane contacts the filter paper, and a device for detecting the change in weight of the cylindrical pool or the cyclopentasiloxane and the time elapsed. For example, after 10 g of surface-modified zinc oxide particles are placed in the cylindrical pool, the cyclopentasiloxane is contacted with the filter paper to measure the weight change of the pool or the cyclopentasiloxane and the time elapsed. Then, the value of A can be obtained based on the weight change, the time elapsed, and the formula (1).

[0137] [Dispersion liquid]

[0138] The dispersion liquid of the present embodiment contains the surface-modified zinc oxide particles of the present embodiment and a dispersion medium. The dispersion liquid can be formed by preparing the surface-modified zinc oxide particles of the present embodiment and mixing them with the dispersion medium.

[0139] In addition, the dispersion liquid of the present embodiment can also preferably contain a paste-like dispersion having a high viscosity.

[0140] The dispersion medium is not particularly limited as long as it can disperse the surface-modified zinc oxide particles. When the surface-modified zinc oxide particles are used for cosmetic purposes, the dispersion medium is not particularly limited as long as it can be formulated into the cosmetic.

[0141] Examples of the dispersion medium include chain polysiloxanes such as dimethylpolysiloxane, methylphenylpolysiloxane, and diphenylpolysiloxane, cyclic polysiloxanes such as octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecamethylcyclohexasiloxane, amino-modified polysiloxane, polyether-modified polysiloxane, alkyl-modified polysiloxane, and modified polysiloxanes such as fluorine-modified polysiloxane, liquid paraffin, squalane, isoparaffin, branched light paraffin, vaseline, and diatomaceous earth. Hydrophobic dispersion media including wax, dodecane, isododecane, tridecane, tetradecane, hexadecane, isohexadecane, octadecane and other hydrocarbon oils; ester oils including isopropyl myristate, hexadecyl isooctanoate, tricaprylin, tri(caprylic / capric)glyceryl, alkyl benzoate (C12-15) and other ester oils; higher fatty acids including lauric acid, myristic acid, palmitic acid, stearic acid and other higher alcohols including lauryl alcohol, cetyl alcohol, stearyl alcohol, octyldodecanol, isostearyl alcohol and other hydrophobic dispersion media. In addition, there can be mentioned alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, 2-butanol, octanol, glycerol, etc.; esters such as ethyl acetate, butyl acetate, ethyl lactate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, γ-butyrolactone, etc.; ethers such as ethyl ether, ethylene glycol monomethyl ether (methyl cellosolve), ethylene glycol monoethyl ether (ethyl cellosolve), ethylene glycol monobutyl ether (butyl cellosolve), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, etc.; benzene, toluene, ethylbenzene, Aromatic hydrocarbons such as 1-phenylpropane, isopropylbenzene, n-butylbenzene, tert-butylbenzene, sec-butylbenzene, o-, m- or p-xylene, 2-, 3- or 4-ethyltoluene; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone; amides such as dimethylformamide, N,N-dimethylacetoacetamide, N-methylpyrrolidone; nitriles such as acetonitrile; natural oils such as oleic acid, jojoba oil, olive oil, coconut oil, grape seed oil, castor oil, rice bran oil, horse oil, mink oil, etc.

[0142] These dispersion media may be used alone or in combination of two or more.

[0143] When the surface-modified zinc oxide particles are used for cosmetic purposes, the dispersion medium preferably uses the above-mentioned linear polysiloxane, the above-mentioned cyclic polysiloxane, the above-mentioned modified polysiloxane, the above-mentioned hydrocarbon oil, the above-mentioned ester oil, the above-mentioned higher fatty acid, the above-mentioned higher alcohol, the above-mentioned natural oil, ethanol, glycerol, etc.

[0144] These dispersion media may be used alone or in combination of two or more.

[0145] The dispersion liquid of the present embodiment may contain commonly used additives within a range that does not impair the characteristics thereof.

[0146] Examples of the additive include preservatives, dispersants, dispersing aids, stabilizers, water-soluble binders, thickeners, oil-soluble drugs, oil-soluble pigments, oil-soluble proteins, and UV absorbers.

[0147] The particle size (d50) at which the cumulative volume percentage of the particle size distribution in the dispersion of this embodiment is 50% can be arbitrarily selected, but is preferably 300 nm or less (0.3 μm or less), more preferably 250 nm or less, and further preferably 200 nm or less. It may also be 150 nm or less or 100 nm or less.

[0148] The lower limit of d50 is not particularly limited, and may be, for example, 20 nm or more, 40 nm or more, or 60 nm or more.

[0149] The upper limit value and the lower limit value of d50 can be arbitrarily combined.

[0150] Furthermore, the particle size (d90) when the cumulative volume percentage of the particle size distribution in the dispersion of the present embodiment is 90% is preferably 350 nm or less, more preferably 300 nm or less, and even more preferably 250 nm or less.

[0151] The lower limit of d90 is not particularly limited, and may be, for example, 60 nm or more, 80 nm or more, or 100 nm or more.

[0152] The upper limit value and the lower limit value of d90 can be combined arbitrarily.

[0153] When the d50 of the dispersion is 300 nm or less, when the cosmetic prepared using the dispersion is applied to the skin, the surface-modified zinc oxide particles are easily evenly distributed, thereby improving the ultraviolet shielding effect, which is preferred. In addition, when the d90 of the dispersion is 350 nm or less, the transparency of the dispersion is high, and the transparency of the cosmetic prepared using the dispersion is also high, which is preferred.

[0154] That is, when d50 and d90 in the dispersion of the present embodiment are within the above ranges, a dispersion having excellent transparency and excellent ultraviolet shielding properties can be obtained. Furthermore, a cosmetic prepared using the dispersion also has excellent transparency and ultraviolet shielding properties.

[0155] As a method for measuring the cumulative volume percentage of the particle size distribution in the dispersion liquid of the present embodiment, for example, there is a method using a dynamic light scattering particle size distribution measuring apparatus (model: LB-550, manufactured by Horiba, Ltd.).

[0156] The content of the surface-modified zinc oxide particles in the dispersion of the present embodiment can be appropriately adjusted according to the properties of the target dispersion.

[0157] When the dispersion of the present embodiment is used in a cosmetic, the content of the surface-modified zinc oxide particles in the dispersion is preferably 30% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more. Furthermore, the content of the surface-modified zinc oxide particles in the dispersion is preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less.

[0158] The upper limit and lower limit of the content of the surface-modified zinc oxide particles in the dispersion may be arbitrarily combined.

[0159] When the content of the surface-modified zinc oxide particles in the dispersion is within the above range, the dispersion can contain a high concentration of surface-modified zinc oxide particles, thereby increasing the degree of freedom in formulating cosmetics produced using the dispersion and adjusting the viscosity of the dispersion within a range that is easy to handle.

[0160] The method for producing the dispersion liquid of the present embodiment is not particularly limited, and for example, a method of mechanically dispersing the surface-modified zinc oxide particles of the present embodiment and a dispersion medium using a known dispersing device can be mentioned.

[0161] The dispersing device can be selected as needed. Examples of the dispersing device include a stirrer, a rotation-revolution mixer, a homomixer, an ultrasonic homogenizer, a sand mill, a ball mill, and a roll mill.

[0162] The dispersion liquid of the present embodiment can be used for coating materials or the like having an ultraviolet shielding function or a gas permeation suppressing function, in addition to cosmetics.

[0163] According to the dispersion of the present embodiment, since the surface-modified zinc oxide particles of the present embodiment are contained, the production efficiency of the dispersion is good and high ultraviolet shielding properties are stably exhibited.

[0164] [Composition]

[0165] The composition of the present embodiment contains the surface-modified zinc oxide particles of the present embodiment, a resin, and a dispersion medium. The composition can be prepared by preparing the surface-modified zinc oxide particles of the present embodiment and mixing the resin and the dispersion medium.

[0166] The content of the surface-modified zinc oxide particles in the composition of this embodiment can be appropriately adjusted according to the properties of the target composition. The content of the surface-modified zinc oxide particles in the composition of this embodiment is, for example, preferably 10% by mass or more and 40% by mass or less, and more preferably 20% by mass or more and 30% by mass or less.

[0167] When the content of the surface-modified zinc oxide particles in the composition is within the above range, the composition can contain a high concentration of the surface-modified zinc oxide particles. Therefore, the properties of the surface-modified zinc oxide particles can be fully obtained, and a composition in which the surface-modified zinc oxide particles are uniformly dispersed can be obtained.

[0168] The dispersion medium is not particularly limited as long as it is a dispersion medium generally used in industrial applications. Examples of the dispersion medium include alcohols such as methanol, ethanol, and propanol, methyl acetate, ethyl acetate, toluene, methyl ethyl ketone, and methyl isobutyl ketone.

[0169] The content of the dispersion medium in the composition of the present embodiment is not particularly limited and can be appropriately adjusted according to the properties of the target composition.

[0170] The resin is not particularly limited as long as it is a resin generally used for industrial purposes. Examples of the resin include acrylic resins, epoxy resins, urethane resins, polyester resins, and silicone resins.

[0171] The content of the resin in the composition of the present embodiment is not particularly limited and can be appropriately adjusted according to the properties of the target composition.

[0172] The composition of the present embodiment may contain commonly used additives within a range that does not impair the properties thereof.

[0173] Examples of the additive include a polymerization initiator, a dispersant, and an antiseptic.

[0174] The method for producing the composition of the present embodiment is not particularly limited, and an example thereof includes a method of mechanically mixing the surface-modified zinc oxide particles of the present embodiment, a resin, and a dispersion medium using a known mixing device.

[0175] Furthermore, there can be mentioned a method of mechanically mixing the dispersion and the resin using a known mixing device.

[0176] Examples of the mixing device include a stirrer, a rotation-revolution mixer, a homomixer, and an ultrasonic homogenizer.

[0177] The composition of this embodiment can be applied to a plastic substrate such as a polyester film by a common coating method such as roll coating, flow coating, spray coating, screen printing, brush coating, dipping, etc. to form a coating film. These coating films can be used as ultraviolet shielding films or gas barrier films.

[0178] According to the composition of the present embodiment, since the surface-modified zinc oxide particles of the present embodiment are contained, the production efficiency of the composition is good and high ultraviolet shielding properties are stably exhibited.

[0179] [Cosmetics]

[0180] The cosmetic of the present embodiment contains at least one of the surface-modified zinc oxide particles of the present embodiment and the dispersion of the present embodiment, and a cosmetic base raw material.

[0181] Here, the cosmetic base raw materials refer to various raw materials that form the main body of cosmetics, and examples thereof include oily raw materials, water-based raw materials, surfactants, powder raw materials, and the like.

[0182] Examples of the oily raw material include fats and oils, higher fatty acids, higher alcohols, and ester oils.

[0183] Examples of the aqueous raw material include purified water, alcohol, and a thickener.

[0184] Examples of the powder raw material include color pigments, white pigments, pearlescent agents, and extender pigments.

[0185] In the present embodiment, the raw material of the cosmetic base may preferably be an oily raw material, a powdery raw material, or an oily raw material and a powdery raw material, and an oily raw material may more preferably be used.

[0186] The cosmetics of this embodiment may refer to oily cosmetics, emulsion-type cosmetics containing surface-modified zinc oxide particles in an oil phase, powdered solid cosmetics formed by mixing surface-modified zinc oxide particles with an oil agent and then removing the oil agent, and the like, which are cosmetics containing surface-modified zinc oxide particles in the oil component (oil phase) during the manufacturing process or in the final form.

[0187] The emulsion-type cosmetic may be an O / W emulsion or a W / O emulsion.

[0188] In other words, the cosmetic of the present embodiment preferably contains at least one of the surface-modified zinc oxide particles of the present embodiment and the dispersion of the present embodiment in the oil component or the oil phase.

[0189] The oil component used in the oil phase of an oily cosmetic or emulsion is not particularly limited as long as it is an oil component commonly used in cosmetics, and examples thereof include silicone oil, fats and oils, higher fatty acids, higher alcohols, ester oils, and natural oils.

[0190] Furthermore, the cosmetic of the present embodiment may contain the aqueous raw material, surfactant, powder raw material, etc. as long as the properties thereof are not impaired.

[0191] The cosmetic of the present embodiment is obtained, for example, by blending the surface modified zinc oxide particles or dispersion of the present embodiment into a base of cosmetics such as lotion, cream, sunscreen, foundation, lipstick, blush, eye shadow, etc. in the same manner as conventionally.

[0192] The cosmetic of the present embodiment is obtained by blending the surface-modified zinc oxide particles of the present embodiment into an oil phase to form an O / W type or W / O type emulsion, and blending the emulsion with the raw materials of the cosmetic.

[0193] The content of the surface-modified zinc oxide particles in the cosmetic of the present embodiment can be appropriately adjusted according to the characteristics of the target cosmetic. For example, the lower limit of the content of the surface-modified zinc oxide particles can be 0.01% by mass or more, 0.1% by mass or more, or 1% by mass or more. In addition, the upper limit of the content of the surface-modified zinc oxide particles can be 50% by mass or less, 40% by mass or less, or 30% by mass or less.

[0194] The upper limit and lower limit of the content of the surface-modified zinc oxide particles in the cosmetic may be arbitrarily combined.

[0195] Hereinafter, sunscreen cosmetics will be specifically described as an example of cosmetics.

[0196] In order to effectively shield ultraviolet rays (especially long-wavelength ultraviolet rays (UVA)) and obtain a good feeling of use with less powdery or astringent feeling, the lower limit of the content of the surface-modified zinc oxide particles in the sunscreen cosmetic is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and further preferably 1% by mass or more. In addition, the upper limit of the content of the surface-modified zinc oxide particles in the sunscreen cosmetic can be 50% by mass or less, 40% by mass or less, or 30% by mass or less. The upper limit and lower limit of the content of the surface-modified zinc oxide particles in the sunscreen cosmetic can be arbitrarily combined.

[0197] Sunscreen cosmetics may contain hydrophobic dispersion medium, inorganic fine particles or inorganic pigments other than surface-modified zinc oxide particles, hydrophilic dispersion medium, oil, surfactant, moisturizer, thickener, pH adjuster, nutrient, antioxidant, fragrance, etc. as needed.

[0198] Examples of the hydrophobic dispersion medium include hydrocarbon oils such as liquid paraffin, squalane, isoparaffin, branched light paraffin, vaseline, and ozokerite; ester oils such as isopropyl myristate, cetyl isooctanoate, and tricaprylin; silicone oils such as decamethylcyclopentasiloxane, dimethylpolysiloxane, and methylphenylpolysiloxane; higher fatty acids such as lauric acid, myristic acid, palmitic acid, and stearic acid; and higher alcohols such as lauryl alcohol, cetyl alcohol, stearyl alcohol, hexyldodecanol, and isostearyl alcohol.

[0199] Examples of inorganic fine particles or inorganic pigments other than the surface-modified zinc oxide particles contained in cosmetics include calcium carbonate, calcium phosphate (apatite), magnesium carbonate, calcium silicate, magnesium silicate, aluminum silicate, kaolin, talc, titanium oxide, aluminum oxide, yellow iron oxide, γ-iron oxide, cobalt titanate, cobalt violet, silicon oxide, and the like.

[0200] Sunscreen cosmetics may further contain at least one organic ultraviolet light absorber.

[0201] Examples of the organic ultraviolet absorber include benzotriazole ultraviolet absorbers, benzoylmethane ultraviolet absorbers, benzoic acid ultraviolet absorbers, anthranilic acid ultraviolet absorbers, salicylic acid ultraviolet absorbers, cinnamic acid ultraviolet absorbers, and silicone cinnamic acid ultraviolet absorbers.

[0202] Examples of the benzotriazole-based ultraviolet absorber include 2,2′-hydroxy-5-methylphenylbenzotriazole, 2-(2′-hydroxy-5′-tert-octylphenyl)benzotriazole, and 2-(2′-hydroxy-5′-methylphenyl)benzotriazole.

[0203] Examples of the benzoylmethane ultraviolet absorber include dibenzalazine, anisyl methane, 4-tert-butyl-4′-methoxydibenzoylmethane, 1-(4′-isopropylphenyl)-3-phenylpropane-1,3-dione, and 5-(3,3′-dimethyl-2-norbornylidene)-3-pentan-2-one.

[0204] Examples of the benzoic acid-based ultraviolet absorber include para-aminobenzoic acid (PABA), PABA monoglyceride, N,N-dipropoxy PABA ethyl ester, N,N-diethoxy PABA ethyl ester, N,N-dimethyl PABA ethyl ester, N,N-dimethyl PABA butyl ester, and N,N-dimethyl PABA methyl ester.

[0205] Examples of the anthranilic acid-based ultraviolet absorber include homomenium N-acetylanthranilate.

[0206] Examples of the salicylic acid-based ultraviolet absorber include amyl salicylate, menthyl salicylate, homomenthyl salicylate, octyl salicylate, phenyl salicylate, benzyl salicylate, and p-2-propanolphenyl salicylate.

[0207] Examples of the cinnamic acid-based ultraviolet absorber include octyl methoxycinnamate (ethylhexyl methoxycinnamate), di-p-methoxycinnamic acid-mono-2-ethylhexanoic acid glyceryl ester, octyl cinnamate, ethyl 4-isopropylcinnamate, methyl 2,5-diisopropylcinnamate, ethyl 2,4-diisopropylcinnamate, methyl 2,4-diisopropylcinnamate, propyl p-methoxycinnamate, isopropyl p-methoxycinnamate, isoamyl p-methoxycinnamate, octyl p-methoxycinnamate (2-ethylhexyl p-methoxycinnamate), 2-ethoxyethyl p-methoxycinnamate, cyclohexyl p-methoxycinnamate, ethyl α-cyano-β-phenylcinnamate, 2-ethylhexyl α-cyano-β-phenylcinnamate, and glyceryl mono-2-ethylhexanoyl-di-p-methoxycinnamate.

[0208] Examples of the silicone cinnamic acid ultraviolet absorber include [3-bis(trimethylsilyloxy)methylsilyl-1-methylpropyl]-3,4,5-trimethoxycinnamate, [3-bis(trimethylsilyloxy)methylsilyl-3-methylpropyl]-3,4,5-trimethoxycinnamate, [3-bis(trimethylsilyloxy)methylsilylpropyl]-3,4,5-trimethoxycinnamate, [3-bis(trimethylsilyloxy)methylsilylbutyl]-3,4,5-trimethoxycinnamate, [3-tris(trimethylsilyloxy)silylbutyl]-3,4,5-trimethoxycinnamate, and [3-tris(trimethylsilyloxy)silyl-1-methylpropyl]-3,4-dimethoxycinnamate.

[0209] Examples of organic ultraviolet absorbers other than the above include 3-(4'-methylbenzylidene)-d,l-camphor, 3-benzylidene-d,l-camphor, urocannic acid, ethyl urocannic acid, 2-phenyl-5-methylbenzoxazole, 5-(3,3'-dimethyl-2-nitrobornyl)-3-pentan-2-one, silicone-modified ultraviolet absorbers, and fluorine-modified ultraviolet absorbers.

[0210] According to the cosmetic of the present embodiment, since the surface-modified zinc oxide particles of the present embodiment are contained, the cosmetic can be easily dispersed in an oil component, so the production efficiency is good, and a high ultraviolet shielding property is stably exhibited.

[0211] Example

[0212] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0213] [Example 1]

[0214] "Preparation of surface-modified zinc oxide particles"

[0215] Mixed with a specific surface area of ​​21.3m 2 / g、b * 33.3 parts by mass of 3.33 zinc oxide particles (manufactured by Sumitomo Osaka Cement Co., Ltd.), 2.0 parts by mass of octyltriethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-3083), 0.4 parts by mass of pure water, and 64.3 parts by mass of isopropyl alcohol.

[0216] Next, the mixed solution was dispersed for 3 hours using a bead mill. The dispersion conditions were set at a rotation speed of 2500 rpm and a temperature of 20°C.

[0217] The dispersion liquid from which the beads were removed was subjected to solid-liquid separation and dried at 80° C. for 2 hours to obtain the surface-modified zinc oxide particles of Example 1.

[0218] "Determination of the specific surface area of ​​surface-modified zinc oxide particles"

[0219] The specific surface area of ​​the surface-modified zinc oxide particles of Example 1 was measured using a fully automatic specific surface area measuring device (trade name: Macsorb HM Model-1201, manufactured by MOUNTECH Corporation).

[0220] In addition, the permeability coefficient and b of the particles were determined by the following method: * .

[0221] "Determination of the penetration rate coefficient of cyclopentasiloxane into surface-modified zinc oxide particles"

[0222] The permeation rate coefficient of cyclopentasiloxane to the surface-modified zinc oxide particles was measured by the following procedure using PENETO ANALYZER (model: PNT-N) manufactured by Hosokawa Micron Corporation.

[0223] 10 g of surface-modified zinc oxide particles were filled into a cylindrical cell with a diameter of 36 mm, the bottom of which was a filter paper (model: quantitative filter paper No. 7, manufactured by ADVANTEC) as a measuring cell. 200 g of an aluminum weight was placed on the filled surface-modified zinc oxide particles and left to stand for 1 minute. Then, after removing the weight, a container containing cyclopentasiloxane as a liquid medium was raised by a lifting device so that the cyclopentasiloxane was in contact with the bottom of the cell (filter paper), and the penetration rate was measured.

[0224] The results are shown in Table 1.

[0225] "Surface modified zinc oxide particles * Determination of

[0226] The b value of the surface-modified zinc oxide particles of Example 1 was measured using a spectrocolorimeter (Spectro Color Meter SE7700 manufactured by Tokyo Denshoku Industries Co., Ltd.). * The light source is D65, and the reflection (light 2 degree field of view) measurement condition is The diameter was measured.

[0227] Regarding the measurement sample, 10 g of the surface-modified zinc oxide particles of Example 1 were placed in a 30 mL spiral tube, which was tapped 30 times on a table, and the bottom surface of the spiral tube was used as the measurement surface.

[0228] "Preparation of dispersion liquid"

[0229] 10 g of the surface-modified zinc oxide particles of Example 1, 88 g of cyclopentasiloxane (manufactured by Dow Toray Industries, Inc., model: DOWSIL SH245 Fluid), and 2 g of polyglyceryl-3 polydimethylsiloxyethyl dimethicone (manufactured by Shin-Etsu Chemical Co., Ltd., model: KF-6106) were mixed to obtain a mixed solution.

[0230] Next, the mixed solution was dispersed using a homogenizer (manufactured by IKA Corporation, ULTRA-TURRAX (registered trademark) series: T25 basic) at 9500 rpm for 5 minutes to obtain a dispersion of Example 1.

[0231] "Evaluation of dispersibility based on particle size distribution"

[0232] The dispersion liquid of Example 1 was diluted with cyclopentasiloxane so that the content of the surface-modified zinc oxide particles became 0.01 mass %, thereby preparing a measurement liquid.

[0233] Using this measurement liquid, d50 was measured using a laser diffraction / scattering particle size distribution analyzer (manufactured by Horiba, Ltd., model: LA-920).

[0234] In addition, the particle size (d10) when the cumulative volume percentage of the particle size distribution is 10% and the particle size (d90) when the cumulative volume percentage of the particle size distribution is 90% were measured in the same manner as d50. The results are shown in Table 1.

[0235] "Evaluation of the transparency of dispersion liquid"

[0236] The dispersion of Example 1 was diluted with cyclopentasiloxane so that the concentration of the surface-modified zinc oxide particles became 0.005 mass %.

[0237] The linear transmittance T1 (%) at 360 nm and 550 nm and the total transmittance T2 (%) at 360 nm and 550 nm of the diluted solution were measured using an ultraviolet-visible-near-infrared spectrophotometer (manufactured by JASCO Corporation, model: V-770).

[0238] A low transmittance at 360 nm indicates high ultraviolet shielding properties, and thus a low transmittance at 360 nm is preferred.

[0239] A high transmittance at 550 nm indicates high transparency, and thus a high transmittance at 550 nm is preferably used.

[0240] [Example 2]

[0241] In Example 1, a specific surface area of ​​24.2 m 2 / g、b *Instead of using zinc oxide particles with a specific surface area of ​​21.3 m 2 / g、b * Surface-modified zinc oxide particles of Example 2 were obtained in the same manner as in Example 1 except that the zinc oxide particles had a g / cm3 of 3.33.

[0242] The specific surface area, permeation velocity coefficient and b were measured in the same manner as in Example 1. * The results are shown in Table 1.

[0243] The dispersion of Example 2 was obtained in the same manner as in Example 1 except that the surface-modified zinc oxide particles of Example 2 were used instead of the surface-modified zinc oxide particles of Example 1.

[0244] d10, d50, d90, T1, and T2 were measured in the same manner as in Example 1. The results are shown in Table 1.

[0245] [Example 3]

[0246] In Example 1, a specific surface area of ​​38.2 m 2 / g、b * Instead of using zinc oxide particles with a specific surface area of ​​21.3 m 2 / g、b * Surface-modified zinc oxide particles of Example 3 were obtained in the same manner as in Example 1 except that the zinc oxide particles had a g / cm3 of 3.33.

[0247] The specific surface area, permeation velocity coefficient and b were measured in the same manner as in Example 1. * The results are shown in Table 1.

[0248] A dispersion of Example 3 was obtained in the same manner as in Example 1 except that the surface-modified zinc oxide particles of Example 3 were used instead of the surface-modified zinc oxide particles of Example 1.

[0249] d10, d50, d90, T1, and T2 were measured in the same manner as in Example 1. The results are shown in Table 1.

[0250] [Example 4]

[0251] Surface-modified zinc oxide particles of Example 4 were obtained in the same manner as in Example 3 except that the dispersion treatment was performed for 9 hours instead of for 3 hours.

[0252] The product of the centrifugal force and the dispersion time (impulse) during dispersion was about 3 times that of Example 1. The specific surface area, permeation rate coefficient and b * The results are shown in Table 1.

[0253] A dispersion of Example 4 was obtained in the same manner as in Example 1 except that the surface-modified zinc oxide particles of Example 4 were used instead of the surface-modified zinc oxide particles of Example 1.

[0254] d10, d50, d90, T1, and T2 were measured in the same manner as in Example 1. The results are shown in Table 1.

[0255] [Comparative Example 1]

[0256] In Example 3, the surface-modified zinc oxide particles of Comparative Example 1 were obtained in the same manner as in Example 3 except that the dispersion treatment was performed for 5 minutes instead of for 3 hours.

[0257] The product of the centrifugal force and the dispersion time during dispersion (impulse) was about 1 / 40 of that in Example 1. The specific surface area, permeation rate coefficient and b were measured in the same manner as in Example 1. * The results are shown in Table 1.

[0258] A dispersion of Comparative Example 1 was obtained in the same manner as in Example 1 except that the surface-modified zinc oxide particles of Comparative Example 1 were used instead of the surface-modified zinc oxide particles of Example 1.

[0259] d10, d50, d90, T1, and T2 were measured in the same manner as in Example 1. The results are shown in Table 1.

[0260] [Comparative Example 2]

[0261] The specific surface area is 38.2m 2 / g、b * 100 parts by mass of zinc oxide particles with a viscosity of 3.42 were put into a Henschel mixer. While the zinc oxide particles were stirred by the Henschel mixer, a mixed solution of 5 parts by mass of octyltriethoxysilane (trade name: KBE-3083, manufactured by Shin-Etsu Chemical Co., Ltd.), 0.375 parts by mass of pure water, and 7.125 parts by mass of isopropyl alcohol was added. The mixture was mixed in the Henschel mixer and stirred for 1 hour.

[0262] Next, the obtained mixture was pulverized by a jet mill, and the pulverized powder was dried at 100° C., thereby obtaining surface-modified zinc oxide particles of Comparative Example 2.

[0263] The specific surface area, permeation velocity coefficient and b were measured in the same manner as in Example 1. * The results are shown in Table 1.

[0264] A dispersion liquid of Comparative Example 2 was obtained in the same manner as in Example 1, except that the surface-modified zinc oxide particles of Comparative Example 2 were used instead of the surface-modified zinc oxide particles of Example 1.

[0265] d10, d50, d90, T1, and T2 were measured in the same manner as in Example 1. The results are shown in Table 1.

[0266] [Table 1]

[0267]

[0268] The results in Table 1 show that the surface-modified zinc oxide particles of Examples 1 to 4 have smaller d50 and are excellent in ultraviolet shielding properties than the surface-modified zinc oxide particles of Comparative Examples 1 and 2, and have transparency equal to or higher than that of the surface-modified zinc oxide particles of Comparative Examples 1 and 2.

[0269] "Evaluation of dispersibility"

[0270] 1 g of the surface-modified zinc oxide particles of Examples 1 to 4 and Comparative Examples 1 and 2 was slowly added to a spiral tube containing 20 g of cyclopentasiloxane, and the condition of the spiral tube was observed after 20 minutes.

[0271] As a result, it was confirmed that the surface-modified zinc oxide particles of Examples 1 to 4 were dispersed as a whole, whereas a large number of particles were precipitated in the surface-modified zinc oxide particles of Comparative Examples 1 and 2. The results of Example 4 and Comparative Example 2 are shown in FIG. Figure 1 . Figure 1 The spiral tube on the right side of contains the surface-modified zinc oxide particles obtained in Example 4. Figure 1 The spiral tube on the left side of contains the surface-modified zinc oxide particles obtained in Comparative Example 2. Figure 1 As shown, in Example 4, it was confirmed that the entire surface-modified zinc oxide particles were dispersed. On the other hand, in Comparative Example 2, it was confirmed that a large amount of surface-modified zinc oxide particles were precipitated.

[0272] That is, it was found that the surface-modified zinc oxide particles of Examples 1 to 4 whose permeation rate coefficient of cyclopentasiloxane was within a predetermined range were easily dispersed in the dispersion medium even when the dispersion energy was small during the preparation of the cosmetic.

[0273] Industrial Applicability

[0274] The present invention can provide a surface-modified zinc oxide particle which is easy to be blended into an oily cosmetic and has excellent transparency and ultraviolet shielding properties. The surface-modified zinc oxide particle of the present invention has excellent dispersibility and thus excellent ultraviolet shielding properties, and also has a transparency equal to or higher than that of conventional particles, and therefore has great industrial value when used in cosmetics.

Claims

1. A surface-modified zinc oxide particle having a silane coupling agent on the surface, wherein the silane coupling agent has an alkoxy group, characterized in that: The permeation rate coefficient A of the cyclopentasiloxane represented by A in the following formula (1) with respect to the surface-modified zinc oxide particles is 5.0×10 -2 g 2 / s or more and 1.0×10 2 g 2 / s or less, W 2 =A·t (1) Where W is the penetration weight in g, and t is the time in s.

2. The surface-modified zinc oxide particles according to claim 1, characterized in that L * a * b * b in the chromaticity diagram of the color system * 4.0 or more and 18 or less.

3. The surface-modified zinc oxide particles according to claim 1 or 2, characterized in that The silane coupling agent is at least one selected from the group consisting of alkylalkoxysilane, allylalkoxysilane, polysiloxane having an alkyl group at a side chain, and polysiloxane having an allyl group at a side chain.

4. The surface-modified zinc oxide particles according to claim 1 or 2, characterized in that The silane coupling agent is at least one selected from the group consisting of octyltriethoxysilane, octyltrimethoxysilane, and dimethoxydiphenylsilane-triethoxyoctanoylsilane cross-linked polymer.

5. The surface-modified zinc oxide particles according to claim 1 or 2, characterized in that Obtained as follows: A mixed liquid containing 1 mass % to 55 mass % of zinc oxide particles, 40 mass % to 95 mass % of a solvent, and a silane coupling agent having an alkoxy group is prepared, The mixed solution is dispersed until the surface modified zinc oxide particles have a b * The temperature is 4.0 or more and 18 or less, and then dried. The dispersion energy applied to the mixed liquid is 100 W·h / kg or more.

6. The surface-modified zinc oxide particles according to claim 5, wherein The mixed liquid also contains water and a catalyst.

7. A dispersion, characterized in that: The method comprises the surface-modified zinc oxide particles according to any one of claims 1 to 4 and a dispersion medium.

8. A cosmetic material, characterized in that: The invention comprises the surface-modified zinc oxide particles according to any one of claims 1 to 4 and a raw material for a cosmetic base.

9. A method for selecting surface-modified zinc oxide particles, which is the method for selecting surface-modified zinc oxide particles according to claim 1, comprising: A step of preparing surface-modified zinc oxide particles having a silane coupling agent on the surface, wherein the silane coupling agent has an alkoxy group; The surface-modified zinc oxide particles are evaluated to obtain the permeation rate coefficient A of cyclopentasiloxane represented by A in the following formula (1) relative to the surface-modified zinc oxide particles, and it is determined whether the coefficient A is within 5.0×10 -2 g 2 / s or more and 1.0×10 2 g 2 / s or less range of processes, W 2 =A·t (1) Where W is the penetration weight in g, t is the time in s; and When the above-mentioned A is within the above-mentioned range, the step of surface-modified zinc oxide particles is selected.

10. The method for selecting surface-modified zinc oxide particles according to claim 9, wherein: The determination process comprises: A step of preparing a cylindrical pool with a diameter of 36 mm and a filter paper at the bottom, a container containing cyclopentasiloxane, a member for raising and lowering the container so that the cyclopentasiloxane contacts the filter paper, and a device for detecting a change in the weight of the cylindrical pool or the cyclopentasiloxane and the elapsed time thereof; After placing 10 g of surface-modified zinc oxide particles in the cylindrical cell, cyclopentasiloxane is brought into contact with the filter paper to measure the weight change of the cell or the cyclopentasiloxane and the elapsed time; and A step of obtaining a value of A based on the weight change, the elapsed time and the formula (1).

Citation Information

Patent Citations

  • Zinc oxide powder and its synthesis

    JP2000095519A

  • Method for producing fine powder of zinc oxide, fine powder of zinc oxide and resin composition containing it

    JP2002284527A

  • Low smell alkylsilylated powder, method for producing the same, silicone oil slurry dispersed with the low smell alkylsilylated powder, and cosmetic mixed with the low smell alkylsilylated powder or the silicone oil slurry

    JP2007051188A

  • Surface-treated zinc oxide particles, dispersion liquid, cosmetic, and zinc oxide particles

    WO2017130632A1

  • Surface-treated metal oxide particle, dispersion, composition and cosmetic

    JP2020050811A